Current state of enterprise risk management practices in the Nigerian banking industry - Dabari, Ishaya John; Saidin, Siti Zabedah (Iosrjournals.org, 2016)
Despite the increasing importance of enterprise risk management in enhancing shareholder value and organisational performance, research on risk management related issues have drawn little attention.The primary aim of this survey is to analyse the current state of ERM practices in the Nigerian banking sector.A cross-sectional data was collected through 722 questionnaires that were distributed to the top, middle and lower level managers in all the commercial banks in Nigeria. The findings revealed that the current focus of ERM efforts and areas of risks that present the greatest threats to the banks are positively significant to the current state of ERM practices. However, development of ERM framework is negatively significant.On the other hand, the motivation for the banks to implement ERM practices is statistically insignificant.The finding also revealed that the current state of ERM practices is not yet complete in place as some banks partially complied with the Central Bank Mandate on ERM implementation.Thus, on that point is a clarion call for the supervisory authorities to secure broad implementation of ERM in all the banks regardless of their status.